Localized fields, global impact: Industrial applications of resonant plasmonic materials. (December 2015) - Dionne, J.A.; Baldi, A.; Baum, B.; Ho, C.-S.; Janković, V.; Naik, G.V.; Narayan, T.; Scholl, J.A.; Zhao, Y.
Abstract: Abstract : From the photoinduced transport of energy that accompanies photosynthesis to the transcontinental transmission of optical data that enable the Internet, our world relies and thrives on optical signals. To highlight the importance of optics to society, the United Nations designated 2015 as "The International Year of Light and Light-based Technologies." Although conventional optical technologies are limited by diffraction, plasmons—collective oscillations of free electrons in a conductor—allow optical signals to be tailored with nanoscale precision. Following decades of fundamental research, several plasmonic technologies have now emerged on the market, and numerous industrial breakthroughs are imminent. This article highlights recent industrially relevant advances in plasmonics, including plasmonic materials and devices for energy; for medical sensing, imaging, and therapeutics; and for information technology. Some of the most exciting industrial applications include solar-driven water purifiers, cell phone Raman spectrometers, high-density holographic displays, photothermal cancer therapeutics, and nanophotonic integrated circuits. We describe the fundamental scientific concepts behind these and related technologies, as well as the successes and challenges associated with technology transfer.